Analisis Tingkat Kebangkrutan Model Altman dan Foster pada Perusahaan Agribisnis di Bursa Efek Indonesia - DESILYA VITA PUSPITA; DWI PUTRA DARMAWAN; I NYOMAN GEDE USTRIYANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Bankruptcy Level of Altman and Foster’s Model Analysis in Plantation Companies in Indonesia Stock Exchange The purpose of bankruptcy level using Altman and Foster’s model analysis at plantation companies in Indonesia Stock Exchange is to anticipate and to predict how bankruptcy may occur in a plantation company. The object of this research is the financial reportsofall 16plantation companies that are registered in the Indonesia Stock Exchange during 2013 - 2014. Data were obtained from the Indonesia Stock Exchange’s website. The result of Altman model in 2013 showed that four companies were categorized to “bankruptcy” level and the same result occurred using the Foster model. The result of Altman model in 2014 showed that eight companies were included into “no bankruptcy’ level meanwhile the Foster model indicated 12 companies.The result of Altman model for financial reports 2013-2014 indicated that four companies were included into “prone to bankrupt” level while there are no companies in this category for the Foster model. However, the results of t-test showed that there isno significant difference of bancruptcy level either using Altman and Foster model. Keywords : bankruptcy analysis, Z-score Altman, Z-score Foster